FACTORS RELATED WITH SEXUAL BEHAVIOR IN INTELLECTUAL DISABILITIES IN SLB (SPECIAL NEEDS SCHOOL) DISTRICTS OF BANTUL, YOGYAKARTA - Shulhan Arief Hidayat; Sri Hartini; Budi Wahyuni, (The Malaysian Journal of Nursing (MJN), 2021)
Background: The prevalence of children with intellectual disabilities is reported to be 1-3% or 30 people out of 1,000 Indonesians. Intellectual disability is characterized by the main characteristic of weak thinking ability. Children with intellectual disabilities do not know what sexuality is, they are less able to adapt to the environment, but they have the same physical development and sexual development characteristics as normal children. Children with intellectual disabilities are at higher risk of having negative sexual behavior compared to normal children. Purpose: Knowing the factors (giving parents education about sexuality, adolescent knowledge about sexuality, parenting style, socioeconomic status, exposure to pornographic media, and alcohol consumption) that are related to sexual behavior in adolescents with intellectual disabilities in Bantul Regency SLB (Special Needs Schools), Yogyakarta. Methods: This study was a cross sectional design. The research subjects were all parents and middle school as well as high school intellectual disabilities students in the SLB of Bantul Regency. Research subjects were recruited using consecutive sampling techniques. The instrument used was a questionnaire giving education by parents about sexuality, adolescent knowledge about sexuality, parenting, sexual behavior and screening using peer problem questionnaires. Data analysis was carried out by Person and Independent Sample T-test. Results: 64 students (72.7%) had high risk sexual behavior. There is a significant relationship between exposure to pornographic media (p = 0,000) and knowledge of adolescents (p = 0.008) with adolescent sexual behavior in intellectual disabilities. There is no significant relationship between alcohol consumption, giving education by parents, parenting and socio-economic status with adolescent sexual behavior of intellectual disabilities. Conclusion: Exposure to pornographic media is the most dominant factor associated with adolescent sexual behavior in intellectual disabilities.